Measuring the Effectiveness of Subsidy Policies in Increasing Electric Vehicle Sales in Indonesia: A Study Based on Sales Data of All Brands and Statistical Methods - Nur Hidayah; Achmad Rusdiana; Andi Muhammad Sadat (International Student Conference on Business, Education, Economics, Accounting, and Management (ISC-BEAM), 2024)
Indonesia's commitment to achieving net zero emissions by 2060 is marked by the issuance of Presidential Regulation No. 55/2019, updated by Presidential Regulation No. 79/2023, concerning the acceleration of the battery electric vehicle (BEV) program for road transportation. This policy includes incentives such as a 10 percent Value-Added Tax (VAT) exemption starting on April 1, 2023, for electric vehicles meeting a minimum Domestic Component Level (TKDN) requirement of 40 percent. Additionally, based on the Ministry of Home Affairs Regulation No. 1/2021, electric vehicles are subject to a tax of only 10 percent of the normal annual tax rate. This study uses sales data of all car brands in Indonesia from 2017 to April 2024 to analyze the impact of these policies. The statistical methods used include the Shapiro-Wilk normality test, the Mann-Whitney U test, and linear regression. The statistical analysis results indicate an increase in electric vehicle sales before and after the policy was implemented. Based on linear regression results, electric vehicle sales increased from 1,187 units per month before the policy to 1,877 units per month after the policy, representing an increase of 58.1 percent. Additionally, the number of electric vehicle models increased from 18 models in 2022 to 44 models in 2023 and 52 models in 2024. The conclusion of this study indicates that the electric vehicle subsidy policy has a significant impact on increasing electric vehicle sales, which is also reflected in the increased variety of electric vehicle models following the implementation of the policy.